Mind over mood change how you feel by changing the way you think - Greenberger, Dennis; Padesky, Christine A. (New York The Guilford Press, 2016)
"Discover simple yet powerful steps you can take to overcome emotional distress--and feel happier, calmer, and more confident. This life-changing book has already helped more than 1,000,000 readers use cognitive-behavioral therapy--one of today's most effective forms of psychotherapy--to conquer depression, anxiety, panic attacks, anger, guilt, shame, low self-esteem, eating disorders, substance abuse, and relationship problems. Revised and expanded to reflect significant scientific developments of the past 20 years, the second edition contains numerous new features: expanded content on anxiety; chapters on setting personal goals and maintaining progress; happiness rating scales; gratitude journals; innovative exercises focused on mindfulness, acceptance, and forgiveness; new worksheets; and much more,"--Amazon.com.
How "Mind over mood" can help you -- Understanding your problems -- It's the thought that counts -- Identifying and rating moods -- Setting personal goals and noticing improvement -- Situations, moods, and thoughts -- Automatic thoughts -- Where's the evidence? -- Alternative or balanced thinking -- New thoughts, action plans, and acceptance -- Underlying assumptions and behavioral experiments -- Core beliefs -- Understanding your depression -- Understanding your anxiety -- Understanding your anger, guilt, and shame -- Maintaining your gains and experiencing more happiness.
Includes bibliographical references and index.
Keywords: Cognitive therapy -- Popular works; Affective disorders -- Treatment